72.7k views
5 votes
If y= -2x-1 and x= -2 what is the answer?

User Schuere
by
6.1k points

2 Answers

0 votes
y=-2*(-2)-1
=4-1
y=3

Hope that answer can help you
User David Valentino
by
6.0k points
3 votes
y = -2x -1 and x = -2

Simply plug in -2 for x in our given equation :)

y = -2(-2) - 1

Simplify.

y = 4 - 1

Simplify.

So, y =3

x = -2, y = 3

To check our work, simply plug -2 in for x, and 3 in for y.

y = -2x - 1

(3) = -2(-2) - 1

Simplify.

3 = 4 - 1

3 = 3

Therefore, x = -2, y = 3

~Hope I helped!~
User Bmavus
by
6.2k points